Adolescent Onset of Localized Papillomatosis, Lymphedema, and Multiple Beta-Papillomavirus Infection: Epidermal Nevus, Segmental Lymphedema Praecox, or Verrucosis? A Case Report and Case Series of Epidermal Nevi - Pooja Kadam; Janne Rand; Peter Rady; Stephen Tyring; Jan Stehlik; Monica Sedivcova; Dmitry V. Kazakov; Kathy Ray; Jerome Hill; Richard Agag; J. Andrew Carlson (MDPI AG, 2014)
Herein, we report the case of a 12-year-old female who noted the recent onset of an oval, circumscribed, 10-cm papillomatous plaque affecting the thigh and vulva that showed histologic signs of lymphedema without evidence of secondary lymphedema. The sequencing of genes associated with a delayed onset of lymphedema or epidermal nevi (EN) - GATA2 and GJC2, and HRAS and KRAS, respectively - showed wild-type alleles. Polymerase chain reaction for human papillomavirus (HPV) DNA demonstrated infections with 15 HPV genotypes. Evidence of productive HPV infection, HPV capsid expression, and cytopathic changes was detected. At the 6-month follow-up, no evidence of recurrence was found after complete excision. The analysis of a consecutive series of 91 EN excision specimens revealed that 76% exhibited histologic evidence of lymphostasis. Notably, multiple acrochordon-like EN, which most closely resembled this case, showed similar signs of localized lymphedema. The late onset and evidence of lymphedema favors the diagnosis of congenital unisegmental lymphedema. However, the clinical findings and epidermal changes point to the diagnosis of EN. Moreover, localized verrucosis also accurately describes this patient's cutaneous findings. Based on the above evidence, we postulate that an abnormal development of lymphatics may play a primary role in the pathogenesis of some types of EN and facilitate productive HPV infection. © 2014 S. Karger AG, Basel